The Personality Puzzle - "Funder, David C" (New York, 2016)
The Personality Puzzle continues to lead the market by captivating students with David Funder?s fresh, masterful writing. New material on important research areas such as development and health, streamlined presentation of methods and assessment, and added data graphics presented in a stunning new full-color design make the Seventh Edition an even richer teaching tool.
Keywords: Personality